Clinical use and predictors of outcome in venoarterial extracorporeal membrane (VA ECMO): insights from VERGE (VA ECMO Registry of Germany) - Wengenmayer, Tobias; Staudacher, Dawid; Philipp, Alois; Tigges, Eike; Dettling, Angela; Busse, Hendrik; Kriege, Marc; Padberg, Jan-Sören; Voigt, Ingo; Scherer, Clemens; Graf, Tobias; Scharpf, Dominik; et al. (Clinical research in cardiology, 2025)
The VA ECMO Registry of Germany (VERGE, http://va-ecmo-register.de/ ) is a prospective, multicenter, investigator-driven registry of Venoarterial Extracorporeal Membrane Oxygenation (VA ECMO) all-comers, free from industrial support. VERGE is Germany’s first multicenter registry to systematically gather and analyze data from various centers on the clinical use of VA ECMO. This first report compromises data from 581 VA ECMO patients from 2022. Median age was 60 years, hospital survival was 42% and 25% were female. The leading indication for VA ECMO was extracorporeal cardiopulmonary resuscitation (ECPR) followed by VA ECMO in shock (48.9 and 34.9%, respectively). Hospital survival of ECPR was significantly worse compared to shock (28 and 55%, respectively, p < 0.001). Age, pH, and lactate before cannulation all significantly correlated independently with hospital survival (p < 0.001). In VERGE, no patients with pH below 6.7 or lactate above 25 mmol/l survived.
Gesehen am 01.07.2025